2011
DOI: 10.1017/s0022112010004532
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic/steady streaming from a motionless boundary and related phenomena: generalized treatment of the inner streaming and examples

Abstract: As originally realized by Nyborg (1958), the problem of the inner acoustic/steady streaming can be analyzed in quite general terms. The inner streaming is the one that develops in the high-frequency limit in a thin Stokes (shear-wave) layer at a boundary, in contrast with the outer streaming in the main bulk of the fluid. The analysis consists in expressing relevant inner-streaming characteristics through a given distribution of the acoustic amplitude along the boundary. Here such a generalized treatment is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…The streaming velocity has been calculated for different channel heights indicated by different colors and symbols. The full line is the analytical single-wall solution by Rednikov and Sadhal [15] for a standing acoustic wave parallel to a single planar wall. For all channel heights, the streaming velocity shows an almost linear dependence with positive slope on the equilibrium temperature.…”
Section: B Time-averaged Second-order Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…The streaming velocity has been calculated for different channel heights indicated by different colors and symbols. The full line is the analytical single-wall solution by Rednikov and Sadhal [15] for a standing acoustic wave parallel to a single planar wall. For all channel heights, the streaming velocity shows an almost linear dependence with positive slope on the equilibrium temperature.…”
Section: B Time-averaged Second-order Velocitymentioning
confidence: 99%
“…It was later extended, among others, by Schlicting [10], Nyborg [11], Hamilton [12,13], and Muller et al [14]. Recently, Rednikov and Sadhal [15] have included the temperature dependence of the dynamic viscosity and shown that this can lead to a significant increase in the magnitude of the streaming velocity. In the present work, we present a numerical study of this and related thermoviscous effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use these models without any new contributions. However, so far theoretical treatments of the acoustic streaming generated by standing acoustic waves have not included an analysis of the effect of the vertical sidewall in rectangular microchannels, instead the focus has been on the idealized parallel-plate geometry [9][10][11][12][13][14] or single-wall systems [15][16][17][18]. Also, in most theoretical work either the radiation force or the streaming effects have been studied separately, but not combined with wall effects to obtain a complete description of microparticle * bruus@fysik.dtu.dk acoustophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of acoustic streaming was first described theoretically by Lord Rayleigh [4] in 1884, and has later been revisited, among others, by Schlicting [5], Nyborg [6], Hamilton [7,8], Rednikov and Sadhal [9], and Muller et al [10], to extend the fundamental treatment of the governing equations and to solve the equations for various open and closed geometries.…”
Section: Introductionmentioning
confidence: 99%